Evaluation of The Social Family's Hope Program (PKH): In Argasunya Village, Harjamukti District Cirebon City - Risanti, Sophie; Yulia, Rita; Wulandari, Sri; Erawati, Dedet (PT FORMOSA CENDEKIA GLOBAL, 2025)
The Ministry of Social Affairs of Indonesia launched the Family Hope Program (PKH), a conditional cash transfer aimed at improving the welfare of vulnerable groups. This study evaluates PKH implementation in Argasunya Village, Harjamukti Subdistrict, Cirebon City, due to mismatches between recipients and actual field conditions. Using a descriptive qualitative method, data were collected through participatory observation and literature review. Analysis refers to William N. Dunn’s Evaluation Theory, covering six indicators: Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Accuracy. Findings show that PKH implementation remains suboptimal due to limited public understanding, non-compliance among beneficiaries, and data discrepancies. Facilitators address these issues through persuasive efforts and staged reporting to the Social Service Office, the Mayor, and the Ministry.